2010
DOI: 10.1016/j.jvs.2010.01.030
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of elective endovascular abdominal aortic aneurysm repair in octogenarians and nonagenarians

Abstract: EVAR in octogenarians is associated with high procedural success and low perioperative morbidity and mortality. The midterm results of this study support the use of EVAR in this patient population. Further studies are needed to predict short-term and long-term mortality risk, and treatment for other causes of death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 20 publications
3
34
0
Order By: Relevance
“…Building on this, one observation noted in our study is the higher proportion of female within the octogenarian group. This shares the observation of others in the literature [10,11]. At a superficial level, this may simply represent an upward trend of AAA in female octogenarians.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Building on this, one observation noted in our study is the higher proportion of female within the octogenarian group. This shares the observation of others in the literature [10,11]. At a superficial level, this may simply represent an upward trend of AAA in female octogenarians.…”
Section: Discussionsupporting
confidence: 89%
“…Further investigations or pre-operative interventions were carried out as necessary. Fifty-eight percent of our octogenarian population survived beyond 5 years, which compares favourably with general life expectancy amongst the population in our region although it is notably less than the 64 -92% 5-year survival reported in other studies (3,4,11,12).…”
Section: Discussionsupporting
confidence: 49%
“…Kazmers et al have shown that open aneurysm repair may be beneficial in octogenarians despite the increased mortality associated with their age. 2,3 Furthermore, more recent studies have reported the feasibility of endovascular AAA repair in the elderly. 4e8 Most of these reports, however, have been single institution studies, with results not necessarily generalizable to the entire nation.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that EVAR in octogenarians is associated with high procedural success and low perioperative morbidity and mortality. 38 In the Nonagenarian population Halpern et al report the largest retrospective review of EVAR over a 10-year period. While this remains a small cohort of only 23 patients.…”
Section: The Elderlymentioning
confidence: 99%
“…Their results demonstrated EVAR in octogenarians is associated with low rates of perioperative morbidity and mortality and low long-term aneurysm-related mortality despite the high rates of comorbidities in these patients. 38 …”
Section: Octogenarians-to-nonagenariansmentioning
confidence: 99%